Monitoring System for uninterruptible power supply - Sohiful Anuar, Zainol Murad; Mohd Nazrin, Md Isa; Norazeani, Abdul Rahman (Science Publications, 2009)
Link to publisher's homepage at http://scipub.org/scipub/index.php